THE RELATIONSHIP BETWEEN PROCRASTINATION AND SKEPTICISM OF FEB UNS STUDENTS ON INTEREST IN INVESTING - Kristianto, Yehezkiel Yoga Nugraha Adi; Sumantyo, Riwi; Wijayadne, Devi Rahnjen (Journal of Applied Economics in Developing Countries, 2023)
The habits of students who prefer to procrastinate and doubt something, also influence the attitude in starting an action, one of which is the interest in investing. Student interest in investing is relatively low although the majority of majors in the faculties of economics and business will get knowledge related to the capital market. The purpose of this study was to determine whether there is a relationship between the character of students in procrastination (procrastination) and skepticism (hesitation) of the students of the Faculty of Economics and Business at Sebelas Maret University on the interest in investing in the capital market. This research is a quantitative study with a sample of research using the Stratified Sampling technique, which is based on the level of levels that exist among FEB UNS students (Diploma-3, Strata-1, Masters, and Doctor). The instrument used was an online questionnaire. Data is processed through the SPSS program using multiple regression analysis and cross tabulation. The results showed that procrastination has a negative and significant effect on the interest in investing in students. Meanwhile, skepticism has a positive and significant effect on the interest in investing in students.